PROSPEK GERAKAN RADIKALISME DI INDONESIA - Ruslan Ismail Mage (Populis : Jurnal Sosial dan Humaniora, 2017)
Prospects of radicalism movement in Indonesia. This writing uses literature research methods. The problem in this paper is how is the prospect of radical movement movement in Indonesia? The results of this writing found four interesting things. First, radicalism is not a product of religion, because all religions only teach goodness. The role of religion only invites or advocates good things and prevents things that are bad for society (in the context of Islam known a phrase in Arabic: Amar ma'ruf nahi munkar). Secondly, the main lighter of the radicalism movement is the destruction of the system, supported by the theory of system damage and the theory of structural violence. Third, the peaceful action of movements 411 and 212 denied the radicalism of religious products. Fourth, the prospect of the radicalism movement in Indonesia is more likely due to system damage, rather than due to religious background Keywords: prospect, radicalism, religion, system